Pomegranate extract-loaded surfactant-free zein nanoparticles as a promising green approach for hepatic cancer: optimization and in vitro cytotoxicity - Salma Mohsen; Mohamed Mofreh Bakr; Mohamed A. ElDegwy; Dalia M. N. Abouhussein; Ahmed R. Fares; Aliaa N. ElMeshad (SpringerOpen, 2024)
Abstract Background Hepatic cancer endures a major health scourge as the consequence of a high incidence of > 1 million cases by 2025. Plant-based products are typically effective in ameliorating health conditions. Pomegranate peel extract (PE) with its high polyphenolic content has anticancer effects against different types of cancer. Herein, we aimed to maximize the PE chemotherapeutic efficacy by loading it in a suitable delivery system to overcome the limitations of PE, to control its release and to achieve liver targeting. Method A nanoprecipitation procedure was adopted to incorporate PE into biodegradable and biocompatible natural polymeric zein (ZN)-based nanoparticles (NPs) (PE-ZN NPs). A full factorial design (22 × 31) was developed to study the effects of the formulation variables, namely pH of dispersion, PE-to-ZN ratio and surfactant concentration. Results The optimization revealed a surfactant-free stable PE-ZN NPs formula with a small particle size of 99.5 ± 6.43 nm, high PE encapsulation efficiency % of 99.31% ± 3.64 (w/w) and controlled release of PE over 24 h. Conclusion Moreover, the cytotoxicity of the optimum formula against hepatic cancer HepG2 cell lines was assessed and attained about a 2.5-fold reduction in the inhibitory concentration (IC50) values compared to the free PE affording a promising green platform to combat hepatic cancer. Graphical abstract